High Voltage Engineering: Fundamentals - Kuffel (E); Zaengl (W.S); Kuffel (J) ("17-A / 1, Main Ring RoadLajpat Nagar IV,New Delhi,New Delhi,India-110 024", 2005)
Voltage Transformers
22.5
Keywords: Voltage Transformers